Deficiency of Sustained Attention in ADHD and Its Potential Genetic Contributor MAOA. Issue 9 (July 2018) - Liu, Lu; Cheng, Jia; Su, Yi; Ji, Ning; Gao, Qian; Li, Haimei; Yang, Li; Sun, Li; Qian, Qiujin; Wang, Yufeng
Objective: To investigate the genetic contributors to ADHD sustained attention deficit among noradrenergic genes responsible for the synthesis (dopamine-β-hydroxylase gene, DBH ), transport (norepinephrine transporter gene, NET1 ), reception (alpha-2A adrenergic receptor gene, ADRA2A ), and metabolism (monoamine oxidase A gene, MAOA ) of noradrenalin (NE).Method: A total of 456 children with ADHD and 108 normal controls were included in a digit cancellation test (DCT). DNA was collected from 242 participants and genotyped for 14 single nucleotide polymorphisms (SNPs) of noradrenergic genes.Results: Compared with normal controls, children with ADHD showed a lower total score and higher mean error rate in the DCT, indicating poorer sustained attention function. Analysis of covariance showed an association between MAOA genotypes and ADHD performance in DCT, with poorer performance in risk allele carriers. No association was found for other noradrenergic genes.Conclusion: Children with ADHD presented with a sustained attention deficit compared with normal controls. The sustained attention deficit of children with ADHD may be associated with genetic variant of MAOA .